Poderes : as dimensões central e local - Costa, Paula Pinto (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
One of the current areas of interest of historiography is the study of the history of powers, stemming from the revalorization of political history which took place in the last decades. At the same time, the studies that are focused on local history faced some renovation, namely in their municipal aspect and in the social perspective. The operability of these two spheres of power (central/ local) has been framed in a dynamic process and in an interrelated way, as shown by the most recent studies.